USTADZ YAHYA SEMBIRING'S DAKWAH METHOD IN IMPROVING THE RELIGIOUS UNDERSTANDING OF THE SUGIHEN VILLAGE COMMUNITY, JUHAR DISTRICT - Khairul Fajar; Husni Ritonga (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This qualitative research, designed as a descriptive case study, explores in depth the dakwah method developed by Ustadz Yahya Sembiring in strengthening the religious understanding of the Muslim minority community in Sugihen Village, Juhar District, Karo Regency, while also mapping the obstacles encountered throughout the coaching process. Primary data were obtained through participatory observation and in-depth interviews with the preacher, congregation members, and local traditional figures, then analyzed using the interactive model of Miles and Huberman. The findings reveal that Ustadz Yahya Sembiring consistently practices a wisdom-based (bil hikmah) approach that is highly sensitive to the sociocultural character of the Karo people, operationalized through two complementary methods: bil lisan, expressed through gentle sermons and dialogic study sessions, and bil hal, manifested in exemplary conduct, social assistance, and infrastructure development. Together, these methods have gradually reduced social resistance and sustainably improved the community's religious literacy despite persistent structural and cultural constraints.